PENGARUH PROFESIONALISME DAN DISIPLIN KERJA TERHADAP KINERJA ANGGOTA KEPOLISIAN MELALUI KEPUASAN KERJA PADA POLRES BUTON UTARA - La Ode Musyair; Alida Palilati; La Ode Bahana Adam (Pascasarjana Universitas Halu Oleo, 2022)
This research was conducted with the aim of knowing the effect of Professionalism and Work Discipline on the Performance of Police Members through Job Satisfaction at the North Buton Police Station. The research method used is quantitative descriptive analysis method, and uses SEM analysis method. The data used in this study are primary and secondary data. The population in this study amounted to 100 people with a sampling technique that is using a census. The data were statistically processed using the AMOS program tool.The results of this study indicate that (1) Professionalism has a positive and significant effect on job satisfaction, (2) Work discipline has a positive and significant effect on job satisfaction, (3) Professionalism has a negative and insignificant effect on the performance of police officers, (4) Work discipline has a positive and significant effect on job satisfaction. positive and significant impact on the performance of police officers, (5) job satisfaction has a positive and significant effect on the performance of police officers, (6) professionalism has a significant positive effect on the performance of police officers through job satisfaction. (7) Work discipline has a significant positive effect on the performance of police officers through job satisfaction. The higher the job satisfaction, the higher the performance shown by members of the police at the North Buton Police Station.